A Markov jump model approach to reliable event-triggered retarded dynamic output feedback H∞ control for networked systems. (November 2017) - Wang, Jing; Chen, Mengshen; Shen, Hao; Park, Ju H.; Wu, Zheng-Guang
Abstract: In this paper, the problem of reliable event-triggered H ∞ control is addressed for networked control systems by using retarded dynamic output feedback. The randomness of actuators failures is modeled by a stochastic variable in a Markov jump model framework. To guarantee the considered closed-loop system is stochastically stable with a prescribed H ∞ performance level, a Markov jump event-triggered retarded dynamic output feedback H ∞ controller is designed in this paper, which is the main purpose of our study. By using the stochastic analysis techniques and novel integral inequalities, some sufficient conditions for the solvability of the addressed problem are derived. Finally, an example using a satellite control system model is provided to explain the validity of the proposed method.